ACHIEVING COMPETITIVE ADVANTAGE STRATEGIES THROUGH SOCIAL RESPONSIBILITY DIMENSIONS: AN APPLIED RESEARCH ON A SAMPLE OF BRANCHES OF AL-RAFIDAIN AND AL-RASHID BANKS - A.L. Ibrahim Qais Ibrahim; A. P. Dr. Raheem Sharrad Amer (Scholars Digest Publishing, 2024)
The research aims to determine the impact of social responsibility dimensions in achieving competitive advantage strategies, and a number of branches of Al-Rafidain and Al-Rasheed banks in the capital, Baghdad, were chosen as a field of study according to an analytical study approach. This sample was chosen because of the presence of some social practices in the two banks that may be the cornerstone for formulating social responsibility. The results of the field research were based on an analysis of the reality of the social activities and practices carried out by the two banks for the period from (2015 - 2019), as well as the statistical analysis of the research questionnaire that was prepared for this purpose and distributed to a purposive sample totaling (180), of which (169) were recovered, of which (155) were valid. and (14) invalid forms, and a set of statistical methods were used that were processed with the ready-made statistical program (SPSS). The research came out with a set of conclusions and recommendations, the most prominent of which was that social responsibility has a positive impact, as it achieves several benefits for society and banks together by creating good relationships with shareholders, making banks enjoy credibility, increasing employee loyalty, and combating poverty, unemployment, and pollution.
Keywords: competitive advantage strategies, dimensions of social responsibility, Rafidain and Al-Rasheed Bank.